Avaliação de Métodos para a Estimativa da Acidez Potencial para os solos dos Estados do Rio Grande do Sul e Mato Grosso - Guidotti, Rosane Maria Morales (2013)
Teaching and research activities in different areas of knowledge employ various chemicals substances, some of which are considered dangerous, offering potential risk to those who manipulate it or risk to the environment. The estimation of potential acidity (H + Al) in soils, made by SMP method uses two toxic reagents, p-nitrophenol and potassium chromate. To minimize toxic effect of these reagents, a new method called Sikora was proposed and tested in American soils, with positive results, which replaced them, respectively, by imidazole and the MES (2-N-morpholino ethanesulfonic acid monohydrate), not considered harmful. Sikora method has been tested in some Brazilian soils of Rio Grande do Sul State (RS) and from Central Brazil (Cerrado), and did not present a good correlation. For this reason, the Sikora method was modified and calibrated for these same soils and called Santa Maria buffer (TSM). This study aimed to evaluate the effectiveness of the original Sikora method and his version TSM in the estimation of the soil potential acidity in order to replace the SMP method calibrated for RS and Santa Catarina (SC) States, in a large group of soils, from RS and Mato Grosso (MT) States, with contrasting chemical and physical characteristics. The methods were tested using 110 soil samples from MT and 103 from RS, collected at 0-20 cm depth, in cultivated and uncultivated areas. The results were submitted to correlation analysis and descriptive statistics analysis. A second degree polynomial was adjusted to compare the potential acidity titrated with the pH values obtained with the three methods. Among methods, the higher accuracy in predicting the potential acidity was observed in the following order: SMP > TSM > Sikora, for both soils from RS State Southern and Planalto region as well for those of MT state. In RS state, the TSM method showed to be feasible to estimate potential acidity (H + Al) for soils of both regions, allowing the adoption of a single mathematical model. Only the SMP method presented universality in estimating potential acidity (H + Al) for soils of the two states, RS and MT. Sikora and TSM methods reproduced pH values obtained with SMP method for MT soils and therefore can be used for limestone recommendation. For RS State, the TSM method was more efficient than the Sikora method on the reproduction of soils pH values obtained with the SMP method, being the most suitable to replace SMP method in soil analysis laboratories and therefore to be used on limestone recommendation.